Utilizing Design Factory Principles towards Education 4.0 - Developing Innovation Spaces in Vietnam - Kunnari, Irma; Jussila, Jari; Le, Hoang Anh; Nguyen, Linh Nam; Hoang, An Quoc; Le, My Ha; Ha, Xuan Vinh; Nguyen, Hoang Tuan; Ho, Hoai Nam; Nguyen, Tan Thang (Journal of Technical Education Science, 2022)
In developing Education 4.0, educational institutions need to redesign their learning environments and operations. Connecting real-life challenges from the world of work to the learning processes of the future workforce is crucial in achieving relevant competencies. This article, in the context of the EMVITET Erasmus+ capacity building project, discusses how the Design Factory principles can support the development of innovation spaces for Education 4.0 in Vietnam. In this qualitative practice-based study, three universities and three vocational institutions in Vietnam describe how they have applied the main ideas of the Design Factory concept to their own context. The results show that Design Factory principles can be successfully applied in the Vietnamese higher education and they can help in creating added values for all of the stakeholders including students, teachers and work-life partners. Some challenges in development and respective solutions for them are also discussed.